Modern Business Process Automation: YAWL and its Support Environment - Hofstede, Arthur H. M; Aalst, Wil M. P; Adams, Michael; Russell, Nick (Springer Nature, 2009)
Business Process Automation principles and implementation methods are presented in this comprehensive overview. A wide range of topics are illustrated through the YAWL open-source support environment, providing a sound basis for workflow concepts.